HDAC1 Mediates Immunosuppression of the Tumor Microenvironment in Non-Small Cell Lung Cancer - Fan Y; Ji X; Yuan K; Wu Q; Lou M (Journal of Inflammation Research)
Yongfei Fan,1,2,* Xiang Ji,3,* Kai Yuan,1,2 Qiyong Wu,1,2 Ming Lou1,2 1Department of Thoracic Surgery, The second People’s Hospital of Changzhou, the Third Affiliated Hospital of Nanjing Medical University, Changzhou, 213164, People’s Republic of China; 2Heart and Lung Disease Laboratory, The second People’s Hospital of Changzhou, the Third Affiliated Hospital of Nanjing Medical University, Changzhou, 213164, People’s Republic of China; 3Department of Thoracic Surgery, The First Affiliated Hospital of Bengbu Medical University, Bengbu, 233000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ming Lou; Qiyong Wu, Department of Thoracic Surgery, The second People’s Hospital of Changzhou, the Third Affiliated Hospital of Nanjing Medical University, Changzhou, 213164, People’s Republic of China, Email helloloum@163.com; wqyxycxy@aliyun.comBackground: Studies have demonstrated that histone deacetylase 1 (HDAC1) enables cancer cells to evade killing mediated by cytotoxic T lymphocytes. However, there are no studies on the immunological aspects of HDAC1 in non-small cell lung cancer (NSCLC).Methods: In this research, we used the Cancer Genome Atlas (TCGA) public database combined with tissue microarray (TMA) to investigate HDAC1 expression and prognosis in NSCLC. According to the median value of HDAC1 expression in the TCGA dataset, samples of patients with NSCLC were classified into high- and low-expression cohorts. Subsequently, the biological characteristics of HDAC1 in high- and low-expression cohorts in terms of signaling pathways, immune cell infiltration, immune cell function, and genomic stability were investigated to better understand the effect of HDAC1 in the tumor microenvironment (TME) of NSCLC. Additionally, we selected tissue samples with HDAC1 overexpression in TMA2 and performed immunohistochemical staining of CD8+ T cells to observe the distribution of CD8+ T cells in the tumor.Results: The findings revealed that overexpression of HDAC1 in NSCLC was associated with poor prognosis. Analysis of signaling pathway enrichment indicated that HDAC1 downregulated immune-related signaling pathways in NSCLC. Immune cell infiltration, immune cell function, and genomic stability analyses suggested that the TME alteration mediated by HDAC1 in the high-expression cohort was consistent with the “immune desert” phenotype. Furthermore, CD8+ T immunohistochemical staining experiments of tissue samples with HDAC1 overexpression in NSCLC revealed few CD8+ T cells distributed in the tumor parenchyma and interstitium.Conclusion: Conclusively, our findings from several biological analyses revealed that HDAC1 is overexpressed in NSCLC and induces TME immunosuppression. Keywords: HDAC1, non-small cell lung cancer, immunosuppression, prognosis, tumor microenvironment